Clinical investigation of the interface pressure in the trans-tibial socket with Dermo and Seal-In X5 liner during walking and their effect on patient satisfaction - Ali, S.; Abu Osman, Noor Azuan; Mortaza, N.; Eshraghi, A.; Gholizadeh, H.; Wan Abas, Wan Abu Bakar (2012)
Background: The interface pressure between the residual limb and prosthetic socket has a significant effect on an amputee's satisfaction and comfort. Liners provide a comfortable interface by adding a soft cushion between the residual limb and the socket. The Dermo and the Seal-In X5 liner are two new interface systems and, due to their relative infancy, very little are known about their effect on patient satisfaction. The aim of this study was to compare the interface pressure with these two liners and their effect on patient satisfaction. Methods: Nine unilateral transtibial amputees participated in the study. Two prostheses were fabricated for each amputee, one with the Seal-In liner and one with the Dermo liner. Interface pressure was measured at the anterior, posterior, medial and lateral regions during walking on the level ground. Each subject filled in a Prosthetic Evaluation Questionnaire (PEQ) regarding the satisfaction with the two liners. Findings The mean peak pressures with the Seal-In liner was 34.0 higher at the anterior, 24.0 higher at the posterior and 7.0 higher at the medial regions of the socket (P = 0.008, P = 0.046, P = 0.025) than it was with the Dermo Liner. There were no significant differences in the mean peak pressures between the two liners at the lateral regions. In addition, significant difference was found between the two liners both for satisfaction and problems (P < 0.05). Interpretation There was less interface pressure between the socket and the residual limb with the Dermo liner. The results indicated that the Dermo liner provides more comfort in the socket than the Seal-In liner.